Effect Of Extenders On Seminal Characteristics And Artificial Insemination In German Shepherd Dogs - Thapak, Swadesh; Shrivastava, O.P.; Agrawal, R.G.; Chandrapuria, V.P.; Gupta, V.K.; Sharma , B.L. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The aim of present study was to evaluate the seminal characteristics of German Shepherd dog semen in two dilutors i.e. sodium citrate egg yolk (EYC) and coconut milk extender (CME). Samples were preserved at 50C in sodium citrate egg yolk (EYC) and at room temperature in coconut milk extender (CME) upto 72 hrs. The average morphological abnormalities recorded in EYC were 4.54±0.10, 8.18±0.03, 12±0.15 and 14.96±0.26% and in CME dilutor were 6.98±0.25, 11.35±0.33, 14.87±0.35 and 18.56±0.38% at 0,24,48, and 72 hrs, respectively. Analysis of variance revealed that there was a significant (P<0.05) difference between hours within dilutor and between dilutors at different temperatures. The study revealed that preservability of semen was better upto 72 hrs at 50C in EYC dilutor.